The gravity of China's African export promise - Johnston, Lauren A.; Morgan, Stephen L.; Wang, Yuesheng (Wiley, 2014)
Africa’s largest trade partner, China, criticised for exchanging resources for manufactures, has promised to increase imports and optimise the structure of trade with Africa. Using a gravity model of China’s imports for the years 1995- 2009, we explore potential dynamics for this promise, uniquely accounting for market economy recognition and Taiwan recognition. The former is associated with increased imports, while the latter effect is ambiguous and statistically insignificant. Comparison of projected against actual imports across three growth-path-aligned economic geography typologies - resource-rich; landlocked and resource-poor; coastal and resource-poor – sets out China’s imports trends in an abstract framework of African export potential. We find not only ‘under’ importing across a majority of resource-poor countries. We also find that current trade policy is the least applicable to these comparatively poor exporters’ trade with China. If the latter are to serve a broader catalytic role in Africa’s regional industrial transformation as compared to the role of coastal and resource poor countries in regional economic transformation in Asia and Latin America, China-Africa trade and investment policies may need additional thinking.